Comparative Study of the Corporate Social Responsibility of Rivers State University and University of Port Harcourt, Nigeria - Amadi, Richard Nlemenya; Bayo, Princewill Lekara (NIU Journal of Social Sciences; Vol 6 No 1 (2020): KIU Journal of Social Sciences, Vol. 6 No. 1, March 2020, 2020)
Anchoring on the stakeholders and system's theories, these theories raises some central questions around the paradoxes of communicating about corporate social responsibility (CSR) strategies to enhance organizational effectiveness. Through the qualitative method of obtaining data in interviews, especially from respondents considered relevant to the study; these officers are the unit Heads of the Information, Publication, and Public Relations Units of both the University of Port Harcourt and Rivers State University, Port Harcourt. The researchers compared the corporate social responsibility of these Universities in Port Harcourt. Key to this is that communicating about CSR contributes immensely to the society. This premised however, revealed that both institutions have a similar peripheral CSR strategy that informed the need for a call for the corporate communications unit of both institutions to strategically communicate their corporate activities to the different stakeholder groups potentially interested in the institution from different contexts and sectors. This will help put the institutions of his/her learning on their toes on whether they are up and doing or otherwise. Keyword: Corporate, social responsibility, comparative, Strategy, University of Port Harcourt.